Biological Weed Control for Sustainable Agriculture - Telkar, S. G.; Gurjar, G. N.; Dey, Joy Kumar; Kant, Kamal; Solanki, Shivendu Pratap Singh (International Journal of Economic Plants, 2015)
Biological control utilizes natural living organism, such as insects, herbivorous fish, other animals, disease organisms and competitive plants to limit their growth. In biological control method, it is not possible to eradicate weeds but weed population can be reduced. This method is not useful to control all types of weeds. Introduced weeds are best targets for biological control. Biological control is least harmful to the environment, have no residual effect, relatively cheaper, having comparatively long lasting effect, harmless to non-targeted plants, very effective in control of weeds in non cropped areas. Besides this some of the fish, snails and other animals convert weed vegetation into seafood. This review enumerates various biological control mechanisms used for weed control. The classical examples of biological weed control have also been enlisted.